The Mechanism of Action of the Activated Nitrogen-Containing Metabolites in the Respiratory Tract. Proinflammatory Effect (Part 1) - O.Ye. Abaturov; O.P. Volosovets; T.P. Borysova (Zaslavsky O.Yu., 2015)
The literature review presents a brief description of nitric oxide and nitrogen reactive intermediates. The mechanisms of action of nitric oxide in the respiratory tract are discussed in detail: the impact of high and low concentrations, the direct and indirect effects, protective functions.